2009
DOI: 10.1016/j.cellbi.2009.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Influence of exogenous salicylic acid on flavonolignans and lipoxygenase activity in the hairy root cultures of Silybum marianum

Abstract: Silymarin is one of the most potent antioxidant so far developed from plant sources used as hepatoprotectants. Influence of different concentrations (0, 1, 2, 4, 6 and 8mg/50ml culture) and exposure time (24, 48, 72, 96 and 120h) of salicylic acid on lipoxygenase activity, linoleic acid content, growth and production of silymarin in hairy root cultures of S. marianum were investigated. Detection and identification of flavonolignans was carried out by high performance liquid chromatograph method. Salicylic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 40 publications
1
19
0
1
Order By: Relevance
“…However, the involvement of the octadecanoid pathway in fungal and elicitor-inducible production of secondary metabolite was shown in Catharanthus (Menke et al, 1999) and Silybum (Khalili et al, 2009). Gundlach et al (1992) and Blechert et al (1995) also reported that endogenous jasmonate was accumulated after fungal elicitor treatment of cell cultures.…”
Section: Discussionmentioning
confidence: 99%
“…However, the involvement of the octadecanoid pathway in fungal and elicitor-inducible production of secondary metabolite was shown in Catharanthus (Menke et al, 1999) and Silybum (Khalili et al, 2009). Gundlach et al (1992) and Blechert et al (1995) also reported that endogenous jasmonate was accumulated after fungal elicitor treatment of cell cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, many studies used SA to improve the biosynthesis of important metabolic compounds in cell or hairy-root cultures of different plant species, e.g. jaceosidin and siringin from Saussurea medusa (11), flavonolignans and lipoxygenase from Silybum marianum (12), phenolic metabolism in Matricaria chamomilla (13), metabolic changes of Catharanthus roseus cell cultures (14), podophyllotoxin from Linum album (15), and taxol from Taxus baccata (16). In a previous report, we showed a stimulatory effect of SA on the biosynthesis of asiaticoside in centella cells (17).…”
Section: Results and Conclusion: The Cell Fresh (Dry) Biomass Increamentioning
confidence: 99%
“…Recently, Mustafa et al (2009) showed the effects of SA on the metabolic profile of Catharanthus roseus cell suspensions. SA also increases soluble phenolic compounds in Matricaria chamomilla plants (Kovácik et al 2009) as well as flavolignans in hairy root cultures of Silybum marianum (Khalili et al 2009), but the molecular mechanism underlying the effect of SA on the expression of genes involved in phenolic biosynthesis is still not fully understood. With the aim of gaining insight into the effects of SA on phenolic metabolism as well as improving the biotechnological production of PTOX, we developed cell cultures of PTOX-synthesizing L. album and treated them with SA at the end of the linear growth phase.…”
Section: Introductionmentioning
confidence: 98%